Evaluation Of Antibiotic Use With Quantitative Methods at Sultan Agung Semarang Hospital - Heroweti, Junvidya; Suswanto, Suswanto; Johari, Ahmad Mu’alim (Jurnal Mandala Pharmacon Indonesia, 2024)
Antimicrobial Resistant in Indonesia estimates that the data of deaths due to Antimicrobial Resistant in 2018 is around 700,000 people and this number will continue to increase to 10 million people by 2050. It is necessary to control antibiotic resistance by evaluating the use of antibiotics. The purpose of this study was to determine the quantity of antibiotic use at RSI Sultan Agung Semarang period July-December 2021. This research is observational with a descriptive research design and retrospective data collection. The population used was all medical record data of inpatients in the internal medicine ward who used antibiotics. There were 394 medical records that met the inclusion criteria. Data calculated using the ATC/DDD method is described descriptively and presented in the form of percentages and tables, percentages and tables. The results showed the total DDD value of the antibiotic was 81.56 DDD/100 patient days with a total Length of Stay (LOS) of 2,588 days. Antibiotics with the highest DDD value are Levofloxacin parenteral with a value of every 100 days of hospitalization 20.38 patients received the treatment with a dose of 0.5 grams every day. While antibiotics that enter the 90% DU segment are Levofloxacin (P), Ceftriaxone (P), Moxifloxacin, Cefoperazone Sulbactam (P), Ampicillin Sulbactam (P), Meropenem (P), Metronidazole (P), Cefixime (O), Azitromycin (O), Levofloxacin (O), dan Cefotaxime (P). As a consequence of the possibility of antibiotic resistance, its use should be strictly controlled.